2022
DOI: 10.3390/microorganisms10050980
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Solubilizing Bacteria Isolated from Phosphate Solid Sludge and Their Ability to Solubilize Three Inorganic Phosphate Forms: Calcium, Iron, and Aluminum Phosphates

Abstract: Biofertilizers are a key component of organic agriculture. Bacterial biofertilizers enhance plant growth through a variety of mechanisms, including soil compound mobilization and phosphate solubilizing bacteria (PSB), which convert insoluble phosphorus to plant-available forms. This specificity of PSB allows them to be used as biofertilizers in order to increase P availability, which is an immobile element in the soil. The objective of our study is to assess the capacity of PSB strains isolated from phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 54 publications
4
34
1
4
Order By: Relevance
“…It has been reported that acidification modifies the precipitation/dissolution equilibrium of P and calcium sequestration by organic acids, and this results in P solubilizing and bioavailability [ 5 , 7 ]. Aliyat et al [ 34 ] recently showed the decreasing pH of culture medium through organic acids production (formic, propionic, isobutyric, butyric, isovaleric, caproic, and heptanoic acids) by PSB strains. Benbrik et al [ 19 ] pointed out that in a liquid culture medium, microbial biomass respiration generates CO 2, -producing carbonic acid, creating acidic conditions and, consequently, bacterial growth inhibition, as well solubilization activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that acidification modifies the precipitation/dissolution equilibrium of P and calcium sequestration by organic acids, and this results in P solubilizing and bioavailability [ 5 , 7 ]. Aliyat et al [ 34 ] recently showed the decreasing pH of culture medium through organic acids production (formic, propionic, isobutyric, butyric, isovaleric, caproic, and heptanoic acids) by PSB strains. Benbrik et al [ 19 ] pointed out that in a liquid culture medium, microbial biomass respiration generates CO 2, -producing carbonic acid, creating acidic conditions and, consequently, bacterial growth inhibition, as well solubilization activity.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing soil P concentrations via inorganic and organic soil P mobilization pools involve changes in pH and the release of P-mobilizing compounds such as carboxylates and phosphatases, which are exuded by the roots themselves or by micro-organisms in the rhizosphere. However, the selection of an efficient PSB is crucial, as it practically increases P in the plant rhizosphere (Aliyat et al, 2020). Phosphate solubilization capacity is considered a key factor in isolating highly efficient PSBs from agricultural soils (Aliyat et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the selection of an efficient PSB is crucial, as it practically increases P in the plant rhizosphere (Aliyat et al, 2020). Phosphate solubilization capacity is considered a key factor in isolating highly efficient PSBs from agricultural soils (Aliyat et al, 2020). Among 134 PSB strains from different leguminous plants' rhizosphere in the Fez-Meknes region, only 12 (12) PSBs show phenotypic stability of P solubilization after five successive subcultures in the NBRIP-RP plates.…”
Section: Discussionmentioning
confidence: 99%
“…MPS is the most likely method for increasing plant-accessible P apart from treatment and enzymatic deterioration of natural mixes (Illmer and Schinner, 1992). MPS is the arrival of free P from insoluble mineral phosphates such as calcium phosphate (CaPO4), aluminium phosphate (AlPO4), or ferric phosphate (FePO4) via organic acid temperance (Aliyat et al 2022). PSM organic acid secretion is dependent on carbon (C) source accessibility, ecological conditions, metabolic state and physiology of the life form, and carbon catabolite repression (CCR) (Görke and Stülke, 2008).…”
Section: Phosphate Solubilizationmentioning
confidence: 99%